Yield of varieties of pozolero corn of the ‘elotes occidentales’ race evaluated in High Valleys of Mexico - Santiago-López, Norma; García-Zavala, J. Jesús; Santiago-López, Ulises; Esquivel-Esquivel, Gilberto (Revista Mexicana de Ciencias Agrícolas, 2023)
In the Valles Altos of Mexico, the use of corn (Zea mays L. ) for pozole and the genetic improvement of pozolero corn have focused on using varieties of the races Ancho and Cacahuazintle, locally accepted and adapted to the region, and for this region, the productive response potential of other pozolero varieties originating from other regions of the country is unknown. The objective of this study was to evaluate grain yield and other agronomic variables of 12 varieties of pozolero corn of the Elotes Occidentales race, collected in Salvatierra, Guanajuato, Mexico, in 2018, along with a local variety of ancho corn and another of Cacahuazintle as controls, in order to identify the varieties with outstanding characteristics among the germplasms evaluated and with respect to the commercial controls. The 14 materials were evaluated in three sites of the municipality of Texcoco, State of México, under a randomized complete block design with three repetitions. Significant differences were found for yield between varieties and controls. The varieties yielded from 6.5 to 8.2 t ha-1 and the controls from 3.1 to 7.9 t ha-1. The best varieties of ‘Elotes Occidentales’ exceeded the yield of the control Cacahuazintle by 4 t ha-1 and the control Ancho by 1.5 t ha-1 and the genotypes EOM-1 and EOM-6 were the ones that showed an average yield greater than 8 t ha-1. It was also found that these varieties showed the best characteristics in terms of agronomic behavior and adaptation to the environment for yield (YIE), ear length (EL), number of grains per row (GR) and number of days to male (MF) and female flowering (FF) compared to the commercial pozolero controls Maíz Ancho and Cacahuazintle, with the EOM-1 population having the highest yield with 8.6 t ha-1. The weight of 200 seeds (W200S), plant height (PH) and ear height (EH) were found in the ranges of commercial controls with averages of 2.5 m, 1.6 m and 130 g, respectively. Contrary to the number of rows, the evaluated populations presented a greater number compared to the controls, with the populations EOM-4, EOM-5 and EOM-8 being the most outstanding with 10 rows per ear.